TAX AVOIDANCE: REPUTATIONAL MASK AND BOARD INFLUENCE - Rafael Savio Easter; Eko Santoso (Widya Mandala Surabaya Catholic University, 2026)
Research Purpose. This study examines the relationships among sustainability reporting disclosure, board financial expertise, and tax avoidance practices in the Indonesian food and beverage sector listed on IDX. Research Methods. The study uses a panel regression analysis using secondary data on listed food & beverage companies in IDX, including annual reports and sustainability reports, and director backgrounds from 2021 to 2023. Research Results and Findings. The findings reveal that sustainability reporting disclosure has a significant negative effect on tax avoidance. This suggests that firms with higher levels of sustainability reporting are less likely to engage in tax avoidance activities. In contrast, the financial expertise of board directors does not significantly affect tax avoidance. This study contributes to the literature by providing empirical evidence on the role of sustainability reporting and board characteristics in influencing corporate tax planning strategies. The results indicate that firms that prioritize sustainability and transparency are less inclined to pursue aggressive tax avoidance practices, whereas directors' financial knowledge alone does not necessarily deter such behavior. These findings have important implications for policymakers, regulators, and corporate stakeholders in understanding the drivers of tax avoidance and promoting responsible corporate practice.